Development of Electret Energy Harvester with Micro Spacer - Fujii, K.; Onishi, T.; Sonoda, K.; Fujita, T.; Kanda, K.; Higuchi, K.; Maenaka, K. (2012 Fifth International Conference on Emerging Trends in Engineering and Technology, 2012)
This paper describes a development of MEMS (Micro Electromechanical Systems) -based electrostatic energy harvester for scavenging energy from ambient vibration. Generally, power output of electret harvester is increased with the narrower air-gap between an electret and an opposite electrode. However, electrostatic attraction force between the electret and the opposite electrode is also increased. Hence the gap control is crucial to avoid the pull-in. We measured the displacement of the vibrating mass moved by electrostatic force. As a result, the electric discharge between the Si grid and the base electrode (BE) is occurred when the BE was supplied over 110 V. The vibrating mass is pulled-in at 150 V if the discharge does not occur at the potential. Therefore we proposed and design the electrostatic energy harvester using the micro spacer to prevent the pull-in situation. The size of the spacer is 86 × 86 × 27 μm 3 to prevent the mass fixed by the friction.